The Surface of Imidazolium-Based Ionic Liquids Consists of Two Interfaces - Tóth Ugyonka, Helga; Hantal, György; Szilágyi, István; Idrissi, Abdenacer; Jorge, Miguel; Jedlovszky, Pál (Journal of Physical Chemistry Letters, 2025)
Room temperature ionic liquids (RTILs) are important in a myriad of applications and exhibit fascinating properties arising from a delicate interplay between their ionic and apolar groups. Here, using molecular simulations coupled with intrinsic surface analysis, we reveal how this interplay is responsible for the unique properties of the RTIL surface. Our results show that this surface can be viewed as a superposition of two “interfaces”, one between a hydrophobic layer of cation alkyl chains and the vapor phase, and another between that hydrophobic layer and an ionic fluid composed of polar groups of the cations and anions. Remarkably, the properties of this ionic surface are practically independent of the cation alkyl chain length, suggesting they are a universal feature of imidazolium-based RTILs. This finding has potential implications in the selection and design of RTIL systems for separation applications, which depend on interactions between penetrant molecules and the RTIL surface.
CRIS-Team Scopus Importer:2025-02-28